Heritability of brain volume, surface area and shape: An MRI study in an extended pedigree of baboons - Jeffrey Rogers; Peter Kochunov; Jack L. Lancaster; Wendy Shelledy; David C. Glahn; John Blangero; Peter T. Fox (2007)
Abstract To evaluate baboons ( Papio hamadryas ) as a primate model for the study of the genetic control of brain size and internal structure, we performed high resolution (<500 μm) magnetic resonance imaging on 109 pedigreed baboons. Quantitative genetic analysis of these MR images using a variance components approach indicates that native (untransformed) brain volume exhibits significant heritability among these baboons ( h 2 = 0.52, P = 0.0049), with age and sex also accounting for substantial variation. Using global spatial normalization, we transformed all images to a standard population‐specific reference, and recalculated the heritability of brain volume. The transformed images generated heritability estimates of h 2 = 0.82 ( P = 0.00022) for total brain volume, h 2 = 0.86 ( P = 0.0006) for cerebral volume, h 2 = 0.73 ( P = 0.0069) for exposed surface area of the cerebrum and h 2 = 0.67 ( P = 0.01) for gray matter volume. Regional differences in the genetic effects on brain structure were calculated using a voxel‐based morphometry (VBM) approach. This analysis of regional variation shows that some areas of motor cortex and the superior temporal gyrus show relatively high heritability while other regions (e.g. superior parietal cortex) exhibit lower heritability. The general pattern of regional differences is similar to that observed in previous studies of humans. The present study demonstrates that there is substantial genetic variation underlying individual variation in brain size and structure among Papio baboons, and that broad patterns of genetic influence on variation in brain structure may be similar in baboons and humans. Hum Brain Mapp, 2007. © 2007 Wiley‐Liss, Inc.